Variation in Conflict Behaviours at Departments and Levels of Management - Kar, Brajaballav; Tripathy, Aishwarya (Prabandhan: Indian Journal of Management, 2021)
Conflict within an organization is ubiquitous. Usually, an organization as a whole is taken as the unit of observation in conflict research. However, the task, processes, and relationship as conflict-sources are more likely to be homogeneous within but heterogeneous across functions. We proposed and studied differences of conflict sources, bullying behaviour, emotions and resolution methods, different business functions, and management levels in a stable public sector steel manufacturing organization. The study found the overall level of conflict and bullying behaviour to be low and stress level to be high. Confrontation and negotiation were more used as a conflict-resolution strategy. Age and experience did not have a significant influence on conflict behaviour. However, task, process, and relationship conflicts were significantly different among departments. Significant differences were observed in bullying behaviours and associated emotions. Confrontation was found to be a major conflict resolution strategy that varied across departments. Process conflict varied significantly among different levels of management. The higher level of management experienced greater process conflict. Middle-level managers reported significantly higher withholding of information, unrealistic targets, belittling, criticism, and excessive monitoring. Middle-level managers extensively used confrontation to resolve conflicts.